L’instrumentalisation de l’Union européenne face à la dévolution - Agnès Alexandre-Collier (Revue Française de Civilisation Britannique)
For supporters of devolution, the European Union is a means of by-passing the nation-state, in a context of ‘multi-level governance’ where political authority is distributed among three levels: the supranational level (EU institutions), the national level (the governing central state) and the sub-national level (the ‘peripheral’ nations). For the SNP and Plaid Cymru, which are reluctant to devolution or consider it a necessary step towards independence, Europe has become an essential tool to help them assert Welsh or Scottish nationalism against English centralism. European integration also strengthened their fight for legitimacy and autonomy within the European Union, which has left more political space for local authorities to assert their right to devolution. Both processes of devolution and European integration, which are at first sight inverted, are similar in the way they threaten, or at least question the principle of national sovereignty and in any case lead to the transformation of the governing central state.